MANAJEMEN PENELUSURAN POTENSI WISATA PESISIR DI DESA TAPULAGA KECAMATAN SOROPIA KABUPATEN KONAWE - Tawai, Adrian; Sarmadan, Sarmadan; Asrul Tawulo, Megawati; Yusuf, Bakri; Tuwu, Darmin; Arsyad, Muhammad (....-...., 2023)
Community-based tourism relies on the community as its main component, and the community plays an important role in developing local tourism with the aim of developing local potential related to natural, socio-cultural, and economic conditions. Coastal tourism in Soropia District, Konawe Regency, has not yet reached an optimal level of progress, so it has no impact on increasing people's income in the area. Human resources are an important element in tourism communication, especially in terms of tourism activities related to community care and community welfare. Three main components determine community participation in tourism: the opportunities given to the community to participate in tourism, the community's desire to participate in tourism development, and the community's ability to participate in tourism progress. The solution offered is to inform the community and increase their awareness about the benefits of coastal tourism in Tapulaga Village. Main contribution to the target audience: Increasing understanding of maritime tourism development management by village officials, tourism business actors, tourism workers, and local communities in the coastal area of Soropia District, Konawe Regency